Complications and Long-Term Outcomes of Open Reduction and Plate Fixation of Proximal Humeral Fractures. (4th December 2019) - Robinson, C. Michael; Stirling, Paul H.C.; Goudie, Ewan B.; MacDonald, Deborah J.; Strelzow, Jason A.
Abstract : Background: The optimal treatment of complex proximal humeral fractures in adults remains controversial. We evaluated the risk of complications and the long-term outcomes in patients with a severely displaced fracture or a fracture-dislocation of the proximal part of the humerus treated with open reduction and plate fixation (ORIF). Methods: Between 1995 and 2012, 5, 897 consecutive patients with a proximal humeral fracture were referred to a specialist shoulder clinic for surgical assessment. Indications for surgery included anterior or posterior fracture-dislocation, substantial tuberosity involvement with >1 cm of displacement in a Neer 3 or 4-part fracture configuration, disengagement of the head from the shaft, or severe varus or valgus deformity of the head. All patients who met the surgical criteria and had been followed for 2 years were included, and standardized clinical and radiographic assessments of outcomes were performed. At a median of 10.8 years (range, 5 to 22 years) after ORIF, all surviving cognitively intact patients completed a patient-reported questionnaire assessing functional outcomes and satisfaction. Results: Three hundred and sixty-eight patients (6.2%) met the inclusion criteria and had the appropriate follow-up. The study population had a high rate of complex fracture configurations; 77.2% had tuberosity involvement, 54.1% had complete head-shaft disengagement, and 44.0% had a dislocated head. Eighty-seven patients (23.6%) had postoperative stiffness, 25 (6.8%) had fixation failure/nonunion, and 16 (4.3%) had late osteonecrosis/posttraumatic osteoarthritis; these complications were the reason for the majority of the reoperations in the cohort. The survivorship until any reoperation was 74% at 10 years, but when reoperations for stiffness were excluded, the survivorship was 90% during the same time period. The patients' mean levels of pain, function, and satisfaction with treatment were good to excellent. Conclusions: Our results support the use of primary ORIF in medically fit patients with a severely displaced fracture or a fracture-dislocation of the proximal part of the humerus in centers where the expertise to carry out such treatment exists. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.